Fast Algorithm for Iris Localization Using Daugman Circular Integro Differential Operator - Shamsi, M.; Saad, P.B.; Ibrahim, S.B.; Kenari, A.R. (2009 International Conference of Soft Computing and Pattern Recognition, 2009)
The iris localization is a very important step for iris-recognition. In this step concentric circular outer boundaries of the iris and the pupil in eye's image identify. We enhanced Daugman method to locate the iris by using an Average Square Shrinking Approach. The algorithm is tested using iris images from CASIA database and MMU database. The circle contour sampling parameter has been investigated to find a tradeoff between speed and accuracy of algorithm for different number of points on a circle. The experiments show proposed algorithm can localize the iris faster than other similar methods. Our approach is feasible for online authentication application that need more speed in detection.